Isolating roughness scales of gravel‐bed patches. Issue 8 (14th August 2017) - Bertin, Stephane; Groom, Jane; Friedrich, Heide
Abstract: There is a growing consensus that gravel‐bed roughness should be parameterized based on bed‐surface topography, not only sediment size. One benefit is the possible identification of various spatial scales of surface roughness and evaluation of their respective contributions to flow resistance (and also to bedload transport). The absence of relationships between roughness at the different scales is apparent in previous work, which currently limits roughness parameterization from topography and application in flow modeling. This study examines the use of moving‐window detrending on gravel‐bed digital elevation models (DEMs) for isolating roughness scales and their respective signatures. A large data set of 35 water‐worked gravel‐bed patches from both the laboratory and the field was used for the analysis. The measured bed topography was separated into two distinct DEMs: one representing grains, the other representing small bedforms. For all DEMs, bed‐elevation parameters measuring vertical roughness, imbrication, and spatial correlations were determined. Our results show distinct topographic signatures between grain and bedform DEMs. We show strong positive linear relationships between grain vertical roughness and the size of the bed‐surface material. Surface sediment arrangement also determined bedform shape, with groupings of coarse sediment forming humps on the surface, and finer sediment sheltered in hollows. Patch‐scale vertical roughness could not be estimated simply as the sum of grain and bedform vertical roughness. Instead, our results suggest weighted summation and the existence of universal weighting coefficients. Practical applications for studies on gravel‐bed roughness and flow modeling using DEMs are discussed. Key Points: Moving‐window detrending allows separate examination of grain and bedform roughness contained in patch‐scale DEMs There is a strong correlation between coarse surface sediment size and vertical roughness at both the grain and bedform scale Linear relationships connect the vertical roughness of gravel‐bed patches to grain and bedform vertical roughness